(untitled) (ModaPalavra e-periódico, 2021)
This article deals with the application of an agile approach to projects in service designused in consultancies of the LEMME -UFSC group in partnership with Sebrae/SC. The methodological procedure used for the case study (LEMMEX) adapts an adaptation of the flowchart of Teixeira, Henrique, Braglia & Gonçalves (2018); developed from the approaches of Garret (2010) and Teixeira, Benedet and Hoppe (2015). The standardized method of optimization in the analysis time, greater depth in the relevant items for the proposed solution and more security for decision making.